2020
DOI: 10.15252/embj.2020104464
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic phagocytosis is a compensatory mechanism for microglial dysfunction

Abstract: Microglia are the principal phagocytes that clear cell debris in the central nervous system (CNS). This raises the question, which cells remove cell debris when microglial phagocytic activity is impaired. We addressed this question using Siglech dtr mice, which enable highly specific ablation of microglia. Non-microglial mononuclear phagocytes, such as CNS-associated macrophages and circulating inflammatory monocytes, did not clear microglial debris. Instead, astrocytes were activated, exhibited a proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 73 publications
9
126
0
Order By: Relevance
“…Interestingly, epithelial cells are also related to the potential epithelial origin of some EMP progenitors (Plein et al, 2018 ). Because microglia are macrophage-related cells of the central nervous system and originated from embryonic EMPs (Konishi et al, 2020 ), the majority of postnatal brain microglia expressed eYFP in Rank-Cre; Rosa26eYFP mice. It is well-recognized that RANK is the receptor for RANKL and RANK-RANKL signaling essential for osteoclast differentiation and activation.…”
Section: Unique Expression Profiles Of Emps- and Hscs-derived Macrophmentioning
confidence: 99%
“…Interestingly, epithelial cells are also related to the potential epithelial origin of some EMP progenitors (Plein et al, 2018 ). Because microglia are macrophage-related cells of the central nervous system and originated from embryonic EMPs (Konishi et al, 2020 ), the majority of postnatal brain microglia expressed eYFP in Rank-Cre; Rosa26eYFP mice. It is well-recognized that RANK is the receptor for RANKL and RANK-RANKL signaling essential for osteoclast differentiation and activation.…”
Section: Unique Expression Profiles Of Emps- and Hscs-derived Macrophmentioning
confidence: 99%
“…Complement-3 receptor (CR3), Mac-2 (Glactin-3), CD36, scavenger receptor AI/II (SRAI/II), and triggering receptor expressed on myeloid cells 2 (TREM2) have been proposed as receptors for myelin debris phagocytosis by Mφ and microglia (Kuhlmann et al, 2002;Napoli and Neumann, 2010;Sun et al, 2010;Zhou et al, 2014;Wang et al, 2015;Kopper and Gensel, 2018). The semiprofessional phagocytes, such as astrocytes and endothelial cells, can engulf myelin debris as well (Zhou et al, 2019;Konishi et al, 2020;Wang et al, 2020). We recently demonstrated that newly formed microvessels and lining microvascular endothelial cells in the injured spinal cord can engulf IgG-opsonized myelin debris (Zhou et al, 2019).…”
Section: Phagocytosis Of Cell Debrismentioning
confidence: 99%
“…Correlative light and electron microscopy (CLEM) has brought minimally invasive optical in vivo imaging (usually fluorescence) together with the nanometer resolution of serial section TEM (Transmission Electron Microscopy) or similar EM techniques. A large amount of information about structures and dynamics of the neuroimmune cells can be obtained from the same sample [ 177 , 178 ]. Weinhard and coworkers used CLEM to perform a 3D ultrastructural characterization of organotypic hippocampal cultures, enriching the understanding of the dynamic interaction of postsynaptic spines with microglia [ 179 ].…”
Section: Studying Microglia–neuron Crosstalk With Advanced Microscmentioning
confidence: 99%